The application of vibroseis in VSP logging in Sichuan and Chongqing area. Issue 4 (April 2020) - Ge, Li; Tang, Jian; Zhang, Li; Yong, Jie; Kang, Liang
Abstract: In 1970s, vibroseis was introduced to do seismic exploration in China. After then, vibroseis equipment was researched and produced in China. The electro-control system of the force working on the ground, of vibroseis signal recognizing or installing, and of RT quality-controlling, which is based on the digital self-adapting method, enlarged the application of vibroseis not only the areas but also the quantity in seismic exploration. And then, vibroseis equipment became one of the important seismic equipment. As the producing of shale gas developed, and the traffic conditions improved, the vibroseis equipment and techniques began to work in VSP logging in Sichuan and Chongqing area, south-west of China. The effect of the vibroseis in VSP logging will be analyzed from the theory to the consistence and high S/N ratio of VSP data which be acquired by vibroseis.